2022
DOI: 10.1111/mec.16373
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide sequence data show no evidence of hybridization and introgression among pollinator wasps associated with a community of Panamanian strangler figs

Abstract: The specificity of pollinator host choice influences opportunities for reproductive isolation in their host plants. Similarly, host plants can influence opportunities for reproductive isolation in their pollinators. For example, in the fig and fig wasp mutualism, offspring of fig pollinator wasps mate inside the inflorescence that the mothers pollinate. Although often host specific, multiple fig pollinator species are sometimes associated with the same fig species, potentially enabling hybridization between wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 137 publications
(286 reference statements)
2
18
2
Order By: Relevance
“…In F. rubiginosa , three cryptic species of Pleistodontes imperialis coexist in the same localities while retaining reproductive isolation ( Sutton et al, 2017 ), with Wolbachia identified as the most likely candidate of post-zygotic reproductive isolation ( Haine & Cook, 2005 ). Similarly, no hybridization was detected between pollinating-wasps of genus Pegoscapus in Panama ( Satler et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In F. rubiginosa , three cryptic species of Pleistodontes imperialis coexist in the same localities while retaining reproductive isolation ( Sutton et al, 2017 ), with Wolbachia identified as the most likely candidate of post-zygotic reproductive isolation ( Haine & Cook, 2005 ). Similarly, no hybridization was detected between pollinating-wasps of genus Pegoscapus in Panama ( Satler et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary processes in the fig–pollinator mutualism appear to affect figs and wasps differently. While signatures of hybridization and introgression are present in host fig species ( e.g ., Machado et al, 2005; Renoult et al, 2009; Bruun-Lund et al, 2017; Wilde et al, 2020; Wang et al, 2021a), there is little evidence these processes affect fig wasp pollinators (see Molbo et al, 2003, 2004; Sutton et al, 2017; Satler et al, 2022). This suggests that the processes governing reproductive isolation operate differently within each lineage (figs– plants versus wasps–insects).…”
Section: Discussionmentioning
confidence: 99%
“…In our community of Tetrapus wasps, species are genetically distinct and are highly divergent (Figure 1). This result is consistent with genetic studies of fig wasps, where species typically show little intraspecific divergence but are deeply divergent from other species ( e.g ., Satler et al, 2022). The lack of hybridization in Tetrapus wasps is congruent with results from a recent study of Neotropical strangler fig pollinators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations